THE SOCIAL NECESSITY OF FORMING THE PROFESSIONAL SPEECH CULTURE OF THE EMPLOYEE OF INTERNAL AFFAIRS BODIES (Scientific journal of the Fergana State University, 2023)
The article presents the development of communicative competence of employees of internal affairs bodies, the main and primary tasks of general professional training, the concepts of "professional culture" and "culture", linguistic competence.